The Determinants of Income Smoothing: Study of Indonesian Manufacturing Companies - Sherly Tiana; Karina Harjanto (Conference Series, 2021)
The purpose of this research is to obtain empirical evidence about the effect of profitability, financial, dividend payout ratio and firm size towards income smoothing. The dependent variable of this research is income smoothing measured by Eckel Index. The independent variables of this research are profitability measured by Net Profit Margin (NPM), financial leverage measured by Debt to Assets Ratio (DAR), Dividend Payout Ratio (DPR), and firm size measured by natural logarithm assets. The samples were determined based on purposive sampling method. The sample of this research are 11 manufacture companies that listed in Indonesian Stock Exchange (IDX) in 2016-2018. Secondary data used in this research was analyzed by using logistic regression method. The result of this research are (1) profitability (NPM) has no positive effect towards income smoothing, (2) financial leverage (DAR) has no positive effect towards income smoothing, (3) Dividend Payout Ratio (DPR) has no positive effect towards income smoothing, (4) firm size has significant negative effect towards income smoothing, (5) profitability, financial leverage, Dividend Payout Ratio, and firm size has significant effect towards income smoothing.